Revolutionary subjects : German literatures and the limits of aesthetic solidarity with Latin America - Trnka, Jamie H. (Jamie Helene) (Interdisciplinary German cultural studies, 2015)
"Revolutionary Subjects demonstrates that East and West German literary interests in Latin America coincided with debates about the political relevance of literature in the Cold War. Through a combination of close reading, contextual analysis, and careful theoretical work, Trnka examines textual instances of aesthetic solidarity, which, she argues, anticipated conceptual reorganizations of the world connoted by the transnational or the global" --